2002
DOI: 10.1094/pdis.2002.86.10.1109
|View full text |Cite
|
Sign up to set email alerts
|

Serological Studies Using Polyclonal Antisera Prepared Against the Viral Coat Protein of Four Begomoviruses Expressed in Escherichia coli

Abstract: Polyclonal rabbit antisera were produced to the coat protein of Bean golden mosaic virus Brazil isolate (BGMV), Cabbage leaf curl virus (CabLCV), Tomato yellow leaf curl virus (TYLCV), and Tomato mottle virus (ToMoV), all expressed in Escherichia coli by the pETh expression vector. The expressed coat protein of each virus was purified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis for use as an immunogen. The antisera to BGMV, CabLCV, TYLCV, and ToMoV reacted in indirect (plate-trapping) enzyme-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
20
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
2
20
1
Order By: Relevance
“…Maximum expression of the fusion protein from pMal-PY-CP construct was achieved in E. coli TB1 cells. Higher induction was observed with 0.4 mM IPTG at 37°C for 3 h. Unlike other vector systems [1,6], the fusion protein in the present study was found in the soluble fraction. Whereas the pET-PY-CP clone did not show any visible expression under above conditions.…”
contrasting
confidence: 66%
See 4 more Smart Citations
“…Maximum expression of the fusion protein from pMal-PY-CP construct was achieved in E. coli TB1 cells. Higher induction was observed with 0.4 mM IPTG at 37°C for 3 h. Unlike other vector systems [1,6], the fusion protein in the present study was found in the soluble fraction. Whereas the pET-PY-CP clone did not show any visible expression under above conditions.…”
contrasting
confidence: 66%
“…To overcome these limitations, molecular biology techniques are currently being used to express the viral genes of interest in E. coli and the recombinant antigen is used for the production of PAb. Recombinant antigens for several RNA plant viruses were successfully produced in E. coli [6,7,10], whereas, very few DNA plant viruses have been used for successful expression of recombinant antigen in E. coli [1].Pumpkin yellow vein mosaic virus, a bipartite begomovirus is known in India since 1950s [13] and the virus was characterized based on host range and serology [8]. Further, phylogenetic analysis of DNA-A sequence revealed that PYVMV was synonymous to squash leaf curl China virus (SLCCNV) reported from China [11,12].…”
mentioning
confidence: 99%
See 3 more Smart Citations